Phosphoinositide 3-Kinase Signaling Pathway in Pancreatic Ductal Adenocarcinoma Progression, Pathogenesis, and Therapeutics - Murthy, Divya; Attri, Kuldeep S.; Singh, Pankaj K. (Frontiers in Physiology, 2018)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy characterized by its sudden manifestation, rapid progression, poor prognosis, and limited therapeutic options. Genetic alterations in key signaling pathways found in early pancreatic lesions are pivotal for the development and progression of pancreatic intraepithelial neoplastic lesions into invasive carcinomas. More than 90% of PDAC tumors harbor driver mutations in K-Ras that activate various downstream effector-signaling pathways, including the phosphoinositide-3-kinase (PI3K) pathway. The PI3K pathway also responds to stimuli from various growth factor receptors present on the cancer cell surface that, in turn, modulate downstream signaling cascades. Thus, the inositide signaling acts as a central node in the complex cellular signaling networks to impact cancer cell growth, motility, metabolism, and survival. Also, recent publications highlight the importance of PI3K signaling in stromal cells, whereby PI3K signaling modifies the tumor microenvironment to dictate disease outcome. The high incidence of mutations in the PI3K signaling cascade, accompanied by activation of parallel signaling pathways, makes PI3K a promising candidate for drug therapy. In this review, we describe the role of PI3K signaling in pancreatic cancer development and progression. We also discuss the crosstalk between PI3K and other major cellular signaling cascades, and potential therapeutic opportunities for targeting pancreatic ductal adenocarcinoma.